Local labour market concentration and wages in Ireland - Kevin Devereux; Zuzanna Studnicka (University College Dublin, UCD School of Economics, 2023)
Economic theory predicts that monopsonistic employers suppress wages below the marginal product of labour. We measure local labour market (LLM) concentration in Ireland from 2008 to 2019 using an employment share HerfindahlHirschmann Index (HHI), a proxy for monopsony power. LLM concentration in Ireland has followed a similar pattern to the US and UK since 2008, surging as firms closed during the financial crisis and falling throughout the recovery. There is substantial variation in HHI by region, with the Midlands having the highest average HHI in every year. As elsewhere, workers in concentrated LLMs earn less. To investigate causality we use a leave-one-out instrumental variable design that exploits national trends in firm numbers within industry to predict local HHI. Using this approach we find an elasticity of -0.27, meaning a 10% increase in the HHI reduces earnings by 2.7%.
Keywords: 330; Arbeitsmarkt; Unternehmenskonzentration; Lohn; Kausalanalyse; Irland